2019
DOI: 10.1088/1755-1315/293/1/012007
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation quality of Pennisetum purpureum cv. Mott ensiled with Lactobacillus plantarum and sugarcane molasses in tropic

Abstract: Fermentation quality of Pennisetum purpureum (Schumach) cv. Mott ensiled with Lactobacillus plantarum [(Orla-Jensen) Bergey et al.] and sugarcane molasses in tropical condition was evaluated. Approximately 100 g portion of wilted material chopped into 20 mm lengths packed into plastic film bags and sealed with a vacuum sealer. T0 was untreated silage, T1 silage with 50 μL L. plantarum without molasses, and T2, T3, and T4 treated silage with 50 μL L. plantarum and 1 %, 2 %, and 3 % molasses respectively. The ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The high fiber content will delay the hydrolysis process by fermentatation, i.e. microbes enzyme in rumen resulting lower absorption [8][9][10]. Previous study Sukaryani [11] showed that 4 d fermentations of rice straw with MA-11 started by submersion in alkaline solution improved the crude protein from 5.22 % to 8.23 % and decreased the crude fiber from 54.24 % to 38.83 %.…”
Section: Introductionmentioning
confidence: 99%
“…The high fiber content will delay the hydrolysis process by fermentatation, i.e. microbes enzyme in rumen resulting lower absorption [8][9][10]. Previous study Sukaryani [11] showed that 4 d fermentations of rice straw with MA-11 started by submersion in alkaline solution improved the crude protein from 5.22 % to 8.23 % and decreased the crude fiber from 54.24 % to 38.83 %.…”
Section: Introductionmentioning
confidence: 99%